INFLUENCE OF ASSETS STRUCTURE, ASSET GROWTH, TAXES, AND PROFITABILITY ON CAPITAL STRUCTURE ON MULTIPLE INDUSTRIES - Dessy Natalia Maduwu; Jessy Safitri Sitorus; Josef Ebenezer Simanjuntak (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
The study is conducted to identify how influential the structure of assets, the growth of assets, taxes, as well as the profitability of the structure of the capital in the enterprise sector of various industries the period 2017-2019. Population studies have amounted to 45 companies that listed in Indonesia Stock Exchange (BEI). The sample used is a number of 20 companies multiplied by 3 years, namely 60 samples. The data analysis method used is statistical analysis descriptive and multiple linear regression analysis. The results of this study show that simultaneously asset structure , asset growth , taxes, and profitability have a significant effect on capital structure. Partially, asset structure, asset growth, taxes, and profitability do not have a significant effect on capital structurel